Bio-waste chitosan-derived N-doped CNT-supported Ni nanoparticles for selective hydrogenation of nitroarenes. Issue 30 (17th July 2020) - Advani, Jacky H.; Ravi, Krishnan; Naikwadi, Dhanaji R.; Bajaj, Hari C.; Gawande, Manoj B.; Biradar, Ankush V.
Abstract : In this study, a facile method for the synthesis of leach proof and earth-abundant non-noble Ni nanoparticles on N-doped carbon nanotubes is reported. Abstract : In this study, a facile method for the synthesis of leach proof and earth-abundant non-noble Ni nanoparticles on N-doped carbon nanotubes is reported. The catalyst was synthesized by an impregnation–carbonization method, wherein a Ni-chitosan complex upon carbonization in a 5% H2 /N2 atmosphere at 800 °C yielded Ni-containing N-doped CNTs. Chitosan served as a single source of carbon and nitrogen, and the nanotube growth was facilitated by the in situ formed Ni nanoparticles. The nanocatalyst was thoroughly characterized by several techniques; elemental mapping by SEM and TEM analysis confirmed the uniform distribution of Ni nanoparticles on the surface of N-doped CNTs with an average size in the range of 10–15 nm. The catalyst efficiently reduced a variety of nitroarenes (>99%) into their corresponding amines at a moderate pressure (5 bar) and a comparatively lower temperature (80 °C). Furthermore, the easy recovery of the catalyst using an external magnetic field along with high activity and easy recyclability makes the protocol eco-friendly.